Biochar assisted anaerobic digestion for biomethane production: Microbial symbiosis and electron transfer. Issue 3 (June 2022) - Saif, Irfan; Thakur, Nandini; Zhang, Peng; Zhang, Lihong; Xing, Xiaohong; Yue, Jianwei; Song, Zhongzhong; Nan, Lan; Yujun, Su; Usman, Muhammad; Salama, El-Sayed; Li, Xiangkai
Abstract: Anaerobic digestion (AD) encounters several challenges such as low digestibility of substances and biomethane production. Recently, extensive research has been conducted on biochar (BC) inclusion in the AD to mitigate inhibitors, promotes process stability, and increase biomethane production. However, a comprehensive review enclosing in-depth the effects of BC at each stage of AD, reduction of inhibitors, and microbial dynamics has not been reported. In this review, the influence of BC on the improvement of the AD system at hydrolysis, acidogenesis, acetogenesis, and methanogenesis along with microbial aggregation have been emphasized. The BC can provide a specific surface area for microbial colonization, enrich specific microbes, and enhance direct interspecies electron transfer (DIET). The BC has been reported to shorten the lag phase up to 20–64.4% and increase biomethane production up to 60–90%. The BC promoted the abundance of acetoclasts (including Methanosarcina, Methanosaeta, and Methanothrix ) and hydrogenotrophs ( Methanobacteria and Methanoculleus ). A few reports have applied BC in pilot-scale AD. However, it still needs validation for both technical and economic feasibility. The BC combined AD digestate can serve as a soil conditioner to improve soil properties and promote crop production. Graphical Abstract: ga1 Highlights: Biochar (BC) effect on each stage of anaerobic digestion is reviewed. BC enhances the adsorption of inhibitors and decreases acidification. BC influence on microbial abundance and biofilm formation is interpreted. Direct interspecies electron transfers enhanced methanogenesis.